Research on Offender Decision-Making and Desistance From Crime: A Multi-Theory Assessment of Offender Cognition Change, United States, 2015-2019 - Lloyd, Caleb ([Verlag nicht ermittelbar], 2021)
This study is largely exploratory and observational, with the main goals to understand (a) how cognitions change across time, (b) which cognitions are related to each other, and (c) which cognition measures are related to recidivism. Employing a two-phase program of research, this study sought to answer several research questions about the relationship between cognitions and desistance from crime: What cognitions do probationers self-identify as key beliefs that motivate their desire to desist from crime? What are the psychometric properties of newly developed standardized measures designed to assess desistance cognitions? Do probationers differ in their crime and desistance cognitions and, on average, do these cognitions change across time? How are crime and desistance cognitions related to official-record assessment and outcome data? Specifically, are there associations between self-reported cognitions and risk and strength factors rated by supervision officers? Do crime and desistance cognitions predict future revocations and arrests as hypothesized by rational choice, correctional psychology, and / or desistance theories? Variables include offender's self-report of their personal perception on the costs and benefits of crime, costs and benefits of attempting to stay crime-free, attitudes, impulsive traits, and emotions. A demographic variable is available: participant gender.